Problematyka rozwoju infrastruktury transportu w polskiej polityce regionalnej - Koźlak, Aleksandra (Issues of Transport Infrastructure Development in Polish Regional Policy, 2009)
The main purpose of this paper is presentation of the approach to the development of transport infrastructure in Polish regional policy. The paper analyzes also the impact of transport infrastructure stock on the level of regional development. The investment in transportation infrastructure and changes in accessibility patterns affect regional development and the spatial distribution of economic activities. It is pointed that development of transport infrastructure is one of priorities in regional policy in Poland. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 692-699